2013
DOI: 10.1038/modpathol.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage pulmonary adenocarcinoma (T1N0M0): a clinical, radiological, surgical, and pathological correlation of 104 cases. The MD Anderson Cancer Center Experience

Abstract: The recent proposal for histological subtyping of pulmonary adenocarcinoma by predominant pattern and introduction of the terms adenocarcinoma in situ and minimally invasive adenocarcinoma to replace the term bronchioloalveolar carcinoma by the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society has led us to conduct a study of 104 patients with early-stage primary pulmonary adenocarcinoma (T1N0M0), with a view to histological subtype as defined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…53, 54 Recent studies that have failed to demonstrate significance of adenocarcinoma histologic subtyping used overall survival rather than survival linked to recurrence such as DFS or CIR. 55, 56 Furthermore, a recurrence must be distinguished from a metachronous primary, as may have occurred in the single case of development of an additional lung nodule in a different lobe of the same lung in one of the MIA cases reported by Xu et al 57 As raised in our study, it may also be important to take into consideration if lepidic predominant adenocarcinoma underwent limited resection with a close margin as it can be very difficult to assess lepidic growth at a staple line margin.…”
Section: Discussionmentioning
confidence: 99%
“…53, 54 Recent studies that have failed to demonstrate significance of adenocarcinoma histologic subtyping used overall survival rather than survival linked to recurrence such as DFS or CIR. 55, 56 Furthermore, a recurrence must be distinguished from a metachronous primary, as may have occurred in the single case of development of an additional lung nodule in a different lobe of the same lung in one of the MIA cases reported by Xu et al 57 As raised in our study, it may also be important to take into consideration if lepidic predominant adenocarcinoma underwent limited resection with a close margin as it can be very difficult to assess lepidic growth at a staple line margin.…”
Section: Discussionmentioning
confidence: 99%
“…12 On CT, lung adenocarcinoma may demonstrate variable appearances including pure GGN (ground-glass components only), part-solid nodules or mixed GGN, and solid nodules or masses (no ground-glass components). 13 Serial CT findings have demonstrated that stepwise progression of lesions with ground-glass opacity, manifested as an increase in size or increase of solid components, does occur in select cases and correlates with a potential association between SSNs and peripheral lung adenocarcinomas. 14 As reported by Henschke et al, 6 in a population of high-risk individuals screened with low-dose CT, there is a greater rate of proven malignancy for part-solid (63%) nodules than pure GGN (18%) or solid nodules (7%).…”
Section: Discussionmentioning
confidence: 98%
“…However, many patients, even patients with resectable lung cancer, still have poor prognoses ( 3 ). For lung adenocarcinoma, studies have found that, even for patients with complete surgical resection and in pathologic stage T1 (pathologic-T1, pT1), the treatment effects and prognoses may be significantly different ( 4 ). There is an urgent need to determine reliable prognostic factors that can predict clinical outcomes and more precisely stratify the group of patients susceptible to poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%